ENHANCING INDEPENDENT LEARNING IN MUSIC EDUCATION THROUGH ELECTRONIC RESOURCES - Bobokulova Moxinur Jamshid qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the enhancement of independent learning in music education through the use of electronic resources. The study examines how digital tools, online platforms, and multimedia content can support students in mastering theoretical knowledge, developing practical skills, and fostering creative thinking. The article also highlights strategies for integrating electronic resources into independent study, promoting self-directed learning, and improving students’ professional competencies in music. The findings demonstrate the effectiveness of electronic resources in facilitating interactive, flexible, and personalized learning experiences for music students.